THE INFLUENCE OF ANEMIA ON MATERNAL AND NEONATAL OUTCOMES IN TEEN AGED PREGNANT WOMEN - MARYUM , S; FARUKH , A; GHALIB , F; NAHEED , U (Biological and Clinical Sciences Research Journal, 2023)
This retrospective study, conducted between October 2022 and October 2023 at Maroof International Hospital & Life Care International Hospital in Pakistan, aimed to assess the impact of anemia on neonatal and maternal outcomes in teenage pregnancies. The study included 585 pregnant women aged 13-19 years, with data collected on various parameters such as demographic details, pregnancy-related information, hemoglobin levels during the last trimester, birth weight, gestational age at birth, obstetric complications, neonatal intensive care admissions, and Apgar scores. Among the 585 participants, 212 (36.2%) were identified as having anemia. Further classification revealed that 57.5% experienced mild anemia, 39% had moderate anemia, and 3.5% had severe anemia. Educational status and irregularities in antepartum care showed significant differences between anemic and non-anemic groups (P < 0.05). Anemia was notably higher in women with lower education levels and irregular antenatal care. The study found that anemia significantly increased the risks of postpartum hemorrhage (P=0.005) and postpartum transfusion (P< 0.001). Additionally, infants born to anemic mothers exhibited a significantly higher rate of neonatal intensive care unit (NICU) admission (P<0.001). Maternal anemia was also significantly associated with low birth weight, small for gestational age (SGA), and preterm delivery. However, anemia had no significant impact on Apgar scores. In conclusion, the study underscores the prevalence of anemia in teenage pregnancies and emphasizes its adverse effects on both fetal and maternal outcomes. The findings highlight the urgent need for governmental initiatives to enhance essential healthcare accessibility and improve antenatal care for this vulnerable demographic.